Customer Satisfaction Index (CSI) Analysis Of The Performance Of City Transportation Services Within The Province (AKDP) In Gorontalo Province - Indonesia (International Journal of Scientific Research in Science and Technology, 2025)
Transportation is a vital sector that supports the socio-economic activities of the community, including Angkutan Kota Dalam Provinsi (AKDP) in Gorontalo Province, Indonesia. This study aims to analyze the level of customer satisfaction (Customer Satisfaction Index) towards AKDP service performance in Gorontalo Province, based on parameters in the five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and physical condition (tangible). This study used a survey method with a questionnaire to collect data from 348 AKDP user respondents. The analysis was conducted by measuring CSI and evaluating the performance of each service indicator. The results showed that AKDP CSI in Gorontalo is at a low level or has not met user expectations, with an average score of 53.81%, with a Gab value of -2.07. This shows the need to improve service quality on 5 (five) aspects, especially reliability, tangible, empathy, responsiveness and assurance. This study provides strategic recommendations for AKDP service providers and policy makers to improve transportation performance in Gorontalo.